A tale of two villages - World Agroforestry Centre (World Agroforestry Centre, 2014)
Agroforestry can transform lives and landscapes. Trees and shrubs grown on farms provide fruit, timber, resins, fuelwood and livestock fodder. They also improve soil fertility, regulate water supplies and help farmers adapt to changing climatic conditions. Which begs the question: if agroforestry can bring so many benefits, why don’t we see lots of trees on every farm? Research in the Ethiopian highlands provides some interesting insights into why there are lots of trees in some landscapes, while few in others. The work was part of the USAID-funded Africa RISING (Research in Sustainable Intensification for the Next Generation) programme, which in the Ethiopian Highlands is managed by the International Livestock Research Institute (ILRI).